2010
DOI: 10.1073/pnas.1004952107
|View full text |Cite
|
Sign up to set email alerts
|

LKB1 inhibits lung cancer progression through lysyl oxidase and extracellular matrix remodeling

Abstract: LKB1 loss-of-function mutations, observed in ∼30% of human lung adenocarcinomas, contribute significantly to lung cancer malignancy progression. We show that lysyl oxidase (LOX), negatively regulated by LKB1 through mTOR-HIF-1α signaling axis, mediates lung cancer progression. Inhibition of LOX activity dramatically alleviates lung cancer malignancy progression. Up-regulated LOX expression triggers excess collagen deposition in Lkb1-deficient lung tumors, and thereafter results in enhanced cancer cell prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
168
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(181 citation statements)
references
References 27 publications
(37 reference statements)
8
168
0
2
Order By: Relevance
“…One possible explanation of this disparity may be the small sample size included in that study. Our findings agree well with several previous studies (Gao et al, 2010;Wilgus et al, 2011), which demonstrating that higher expression of LOX is associated with invasion and is a predictor of poor prognosis in lung adenocarcinoma.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…One possible explanation of this disparity may be the small sample size included in that study. Our findings agree well with several previous studies (Gao et al, 2010;Wilgus et al, 2011), which demonstrating that higher expression of LOX is associated with invasion and is a predictor of poor prognosis in lung adenocarcinoma.…”
Section: Discussionsupporting
confidence: 94%
“…Therefore, aberrant LOX expression or enzymatic activity leads to a series of disease predominantly associated with the ECM, as well as in many human cancers. Increasing evidences have shown that LOX is linked to increased invasion and migration of hypoxic NSCLC cell lines in vitro (Sahlgren et al, 2008;Gao et al, 2010;Wei et al, 2012). However, whether there is some association between HIF-1α and LOX, and what role HIF-1α and LOX play in NSCLC has not previously been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous findings show that Nischarin inhibits anchorage-independent growth, which is inhibited by Nischarin (11). LKB1 has also been shown to inhibit anchorage-independent growth (32). Therefore, we asked whether Nischarin and LKB1 have a cooperative effect on inhibiting anchorage-independent growth.…”
Section: Interaction Of Nischarin and Lkb1 In Breast Cancermentioning
confidence: 99%
“…Loss-of-function mutations in LKB1 are common in lung cancer and loss of LKB1 has been observed to correlate with significantly enhanced levels of LOX enzymes. In a mouse model of lung cancer and human non-small cell lung cancer cell lines, loss of LKB1 leads via enhanced mTOR and HIF1a signalling to enhanced LOX activity, increased deposition of collagen and enhanced proliferation possibly caused by increased matrix stiffness [94]. Thus, although the physiological significance of LKB1-LOX crosstalk remains unclear, loss of LKB1 and the consequent dysregulation of LOX activity in the context of tumour tissue has a prominent impact on stromal extracellular matrix remodelling and collagen biology ( figure 3).…”
Section: Loss Of Par-4 Identity Matters In Cancer: Evil Deeds On the mentioning
confidence: 99%
“…Breakdown of BM is considered an essential step for tumour invasion and metastases. However, loss of LKB1 may also exert opposite, stabilizing effects on BMs and extracellular matrix by stimulating expression of the collagen cross-linking enzyme LOX [94]. Also, these effects may benefit tumour progression, at least once the tumour has breached the BM barrier, by increasing the stiffness of the extracellular matrix.…”
Section: (B) Lkb1 and Proteolytic Moulding Of Basement Membrane (I) Lmentioning
confidence: 99%